The role of perception and knowledge in shaping consumer behaviour toward green agro-food products in romania and its effect on well-being - Silviu Gabriel Szentesi; Florentina Simona Barbu; Radu Lucian Blaga; Luminița Bozdog; Vasile Paul Breșfelean (Amfiteatru Economic, 2025)
Understanding the factors influencing consumer behaviour toward green agro-food products is crucial for shaping consumption habits in the interest of sustainable development. The conducted study expanded knowledge on sustainable consumption of green agro-food products by providing new insights for food market actors, derived from the evaluation of consumer behaviour and attitudes. Factors such as consumer perception and knowledge of green agro-food products, the importance of age, income, and children's involvement in issues related to enhancing well-being through sustainable food consumption were analysed. Data were collected through an online questionnaire from a sample of 614 respondents, representative of the studied consumer segment. Structural equation modelling (SEM) was employed to model the complex relationships underlying sustainable consumption behaviour. The study led to the development of a novel model of sustainable food consumption and highlighted how knowledge and perception of green agro-food products - still relatively unknown and understudied in Romania - positively influence attitudes, consumption behaviour, and consumer well-being. The moderation model empirically demonstrated that age, income, and the presence or involvement of children do not optimise the relationship between consumption behaviour and well-being. This research provides valuable insights within a sustainability framework for decision-makers and marketing specialists operating in food markets.
Keywords: Q01; Q1; Q13; Q56; 330; consumption behaviour; green agro-food products; sustainable development; well-being